The Impact of Gadget Use and Parenting Styles on Speech Delays in Early Childhood: A Literature Review - Delmaifanis, Delmaifanis; Fathimah, Nurul; Masitoh, Siti; Lubis, Rosni (Rajaki of Tulip Medika Publisher, 2024)
Dear editorial teamOur article entitled The Impact of Gadget Use and Parenting Styles on Speech Delays in Early Childhood: A Literature Review, discusses the use of gadgets and its relationship with children's speaking ability. The article will be very useful in implementing parenting patterns for mothers, because nowadays with the increasing development of technology, lack of supervision of gadget use has a negative effect on childrenHopefully it can be considered for publication in IJMHSThank you Best Regards. Delmaifanis